The Discovery of Historicity in German Idealism and Historism
VIII, 292 p.
Keywords: German Idealism develops its philosophy of history as the theory of becoming absolute and as absolute knowledge. Historism also originates from Hegel's and Schelling's discovery of absolute historicity as it turns against Idealism's philosophy of history by emphasizing the singular and unique in the process of history. German Idealism and Historism can be considered as the central German contribution to the history of ideas. Since Idealism became most influential for modern philosophy and Historism for modern historiography, they are analyzed in this volume in a collaboration of philosophers and historians. German Idealism is presented in Schelling and its critics Schlegel, Baader, and Nietzsche; Historism in Ranke, Droysen, Burckhardt, and Treitschke. The volume further presents the impact of Idealism and Historism on present German approaches to the philosophy of history and outlines the debates on the possibility of a philosophy of history and on the methodology of the historical sciences.